Effect of excitons on photoconversion efficiency in the p⁺-n-n⁺- and n⁺-p-p⁺-structures based on single-crystalline silicon - Gorban, A.P.; Sachenko, A.V.; Kostylyov, V.P.; Prima, N.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We have performed theoretical simulation of the photoconversion efficiency in silicon solar cells for AM0 conditions with regard to excitonic effects. Along with known effects, we have taken into account both radiative and nonradiative exciton annihilation. They manifest themselves as square-law recombination of electron-hole pairs. It was shown that the effect of nonradiative exciton annihilation on the photoconversion efficiency is particularly profound in p⁺-n-n⁺-structures. In solar cells based on them the total action of all the excitonic effects leads to an about 10% decrease in the limiting value of photoconversion efficiency. At the same time for n⁺-p-p⁺-structures the reduction of this value due to the excitonic effects is about 5%. As a result, their limiting value of photoconversion efficiency is higher than that in p⁺-n-n⁺-structures.